Hybrid method of tolerance design - Foo, Say Wei (2009)
A new method of tolerance design, which we call the Hybrid method that accelerates the attainment of optimal design center, is proposed. The method combines geometry search with statistical process. At the start of the process, the region of acceptability is estimated using boundary search method. A new tolerance region that covers as much of the estimated region of acceptability is determined. The Centers-of- Gravity (CoG) method is then applied to find a new design center. The tolerance region is then progressively reduced to target size while the process of locating the optimal design centers continues. Compared to the popular CoG method, the speed of convergence of the Hybrid method is much faster while the additional computational load is insignificant.